Inside-Out Transcanal Endoscopic Mastoidectomy: Literature Revision - Bessa, Renan Gonçalves; Tsuji, Robinson Koji (International Archives of Otorhinolaryngology, 2023)
Introduction Recently, there have been significant advancements in transcanal endoscopic ear surgery (TEES). The combination of rigid and thin otoendoscopes with high-definition cameras enabled a less invasive transcanal access to the middle ear and a clearer view of the surgical field. Several surgeons have recently published studies about cholesteatoma resection via transcanal endoscopic surgery, even in cases where the disease has extended to the mastoid, requiring transcanal endoscopic mastoidectomy.Objectives To analyze the currently available literature on transcanal endoscopic inside-out mastoidectomy, and to determine its efficacy as a surgical technique by evaluating the disease's relapse/recurrence rate.Data Synthesis Initially, the titles and abstracts of articles identified were analyzed. At this stage, 117 articles were analyzed, 97 of which were excluded for not meeting the inclusion criteria. The 20 remaining articles were further evaluated. The articles were classified on the basis of five levels of scientific evidence.Final Comments The analysis of the studies showed that the transcanal endoscopic approach is effective in providing access to the attic or antrum, especially in cases of sclerotic mastoids. There was only one study with grade A recommendation, which showed the efficacy of endoscopic ear surgery in the treatment of cholesteatoma. Furthermore, there were three studies with grade B recommendation, showing less relapse/recurrence after TEES. More studies with grade A and B recommendations are needed to better evaluate the effectiveness of TEES, especially compared with that of traditional microscopic surgery.
Keywords: grade; endoscopic; recommendation; cholesteatoma; otology; neurotology